2021
DOI: 10.1088/1755-1315/747/1/012101
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the digital books’ usage to improve the XII IPS 3 class students’ motivation at SMAN Pakusari Jember

Abstract: This research aims to determine the effectiveness of the digital books’ usage in increasing student motivation in XII IPS 3 class at SMAN Pakusari Jember. The method used in this research is descriptive qualitative. The use of digital books in learning is useful to make it easier for students to learn and it also can reduce the weaknesses in printed books. The students feel easy and confortable to use them in learning process, so it increases the students’ motivation at XII IPS 3 of SMAN Pakusari. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Smeets et al (2014), revealed that electronic books that are inserted with multimedia features can enrich the experience of reading books if used properly e books can also improve student learning outcomes Siregar et al, 2020).Interactive electronic books are the best alternative that can contribute to improving reading comprehension and reading interest. Electronic books can be combined with innovative learning models that are seen as being able to improve learning outcomes (Diarta et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Smeets et al (2014), revealed that electronic books that are inserted with multimedia features can enrich the experience of reading books if used properly e books can also improve student learning outcomes Siregar et al, 2020).Interactive electronic books are the best alternative that can contribute to improving reading comprehension and reading interest. Electronic books can be combined with innovative learning models that are seen as being able to improve learning outcomes (Diarta et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Reading will be fun if there are interesting things in the reading so that students are better able to understand the meaning of the content of the reading. Students enjoy learning because this digital book involves students in real problems (Diarta et al, 2021;Montero Küpper & Luna Alonso, 2019). The implication of this research is that the use of scrapbook-based digital books has a positive impact because it can increase students' motivation and literacy.…”
Section: Discussionmentioning
confidence: 96%
“…The advantages of e-modules compared to print modules are that e-modules are more interactive, making them easier to navigate, which allow displaying images, audio, video, and animation, and are equipped with formative quizzes that can provide live automatic feedback (Serevina et al, 2018;Yasa, Chrisyarani, and Mudiono, 2018). In addition, the benefits of e-modules are also able to increase students' motivation, tools, or facilities available for conducting evaluations, making learning quality more efficient (Weng et al, 2018;Diarta et al, 2021;Azizah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%